What is the profile of older drivers considered medically unfit to drive? A cross-sectional survey in Western Switzerland (Swiss Medical Weekly, 2018)
OBJECTIVE We aimed to assess how often and for what reasons general practitioners (GPs) consider older drivers medically unfit to drive. METHODS All GPs certified to carry out fitness-to-drive assessments in Geneva (medical assessors, n = 69), as well as a random sample of 500 GPs practising in Vaud, Neuchatel and Jura, were asked to complete a questionnaire about the mean number of assessments per week, the number of negative decisions in the previous year and the main reason for the most recent negative decision. RESULTS Completed questionnaires were returned by 268 respondents (45 medical assessors and 223 other GPs, participation rate: 47%). The mean proportion of drivers with a negative decision was 2.2% (standard deviation [SD] 3.3). The proportion was slightly lower among medical assessors (1.1%, SD 1.3) compared to other GPs (2.3%, SD 3.3, p